2018
DOI: 10.1016/j.jmst.2018.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ZnO/graphene nanolaminate periodicity on their structural and mechanical properties

Abstract: Structural, electronic and mechanical properties of ZnO/Graphene (ZnO/G) nanolaminates fabricated by low temperature atomic layer deposition (ALD) and chemical vapor deposition (CVD) were investigated. We performed scanning and transmission electron microscopy (SEM/TEM), X-ray diffraction (XRD), electron energy loss spectroscopy (EELS), Raman spectroscopy, X-Ray photoelectron spectroscopy (XPS) and nanoindentation to characterize the ZnO/G nanolaminates. The main structural and mechanical parameters of ZnO/G n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…For Fe 3 O 4 /C in Figure a, the peaks at 30.1, 37.1, 53.4, 57.0, 62.5, and 73.9° corresponded to the (220), (222), (422), (511), (440), and (533) crystal planes of Fe 3 O 4 (PDF #19-0629) . The carbon support with crystallinity was observed in ZnO/C (Figure a) at the peak of 29.2°, which was attributed to the activation behavior of ZnCl 2 for the polymerization of the carbon radical C 2 2– . , Further, ZnO/C displayed the typical pattern of hexagonal P63mc ZnO (PDF #36-1451), , owning peaks at 31.8, 34.4, 36.3, 47.5, 56.6, 62.9, and 68.0°, which related to the (100), (002), (101), (102), (110), (103), and (201) crystal planes. The diffraction peaks of Cu 2 O/C at 29.6, 36.4, 42.3, 61.3, and 73.5° indicated the (110), (111), (200), (220), and (311) crystal faces of cubic Pn-3m Cu 2 O (PDF #05-0667).…”
Section: Resultsmentioning
confidence: 93%
“…For Fe 3 O 4 /C in Figure a, the peaks at 30.1, 37.1, 53.4, 57.0, 62.5, and 73.9° corresponded to the (220), (222), (422), (511), (440), and (533) crystal planes of Fe 3 O 4 (PDF #19-0629) . The carbon support with crystallinity was observed in ZnO/C (Figure a) at the peak of 29.2°, which was attributed to the activation behavior of ZnCl 2 for the polymerization of the carbon radical C 2 2– . , Further, ZnO/C displayed the typical pattern of hexagonal P63mc ZnO (PDF #36-1451), , owning peaks at 31.8, 34.4, 36.3, 47.5, 56.6, 62.9, and 68.0°, which related to the (100), (002), (101), (102), (110), (103), and (201) crystal planes. The diffraction peaks of Cu 2 O/C at 29.6, 36.4, 42.3, 61.3, and 73.5° indicated the (110), (111), (200), (220), and (311) crystal faces of cubic Pn-3m Cu 2 O (PDF #05-0667).…”
Section: Resultsmentioning
confidence: 93%
“…14 Improvement of ZnO crystalline structure in the layers with thicknesses below 50 nm was demonstrated in Al 2 O 3 /ZnO and graphene/ZnO nanolaminates, where ZnO layers were deposited on Al 2 O 3 and graphene layers, respectively. [15][16][17][18] In addition to improvement of the crystalline structure, the optical properties of ZnO in the nanolaminate structures were found to be dependent also on charge transfer on the interface between ZnO and Al 2 O 3 , and between ZnO and graphene. [15][16][17][18] Modelling of Al 2 O 3 /ZnO heterostructures confirmed that the combination of ZnO (band gap ~3.3 eV) with a material with larger band gap as Al 2 O 3 (band gap ~ 6eV) results in increase of the photoluminescence (PL) of ZnO in Al 2 O 3 /ZnO heterostructure due to the charge transfer at the interfaces and decrease of the surface potential in ZnO upper layers.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] In addition to improvement of the crystalline structure, the optical properties of ZnO in the nanolaminate structures were found to be dependent also on charge transfer on the interface between ZnO and Al 2 O 3 , and between ZnO and graphene. [15][16][17][18] Modelling of Al 2 O 3 /ZnO heterostructures confirmed that the combination of ZnO (band gap ~3.3 eV) with a material with larger band gap as Al 2 O 3 (band gap ~ 6eV) results in increase of the photoluminescence (PL) of ZnO in Al 2 O 3 /ZnO heterostructure due to the charge transfer at the interfaces and decrease of the surface potential in ZnO upper layers. 16 On the other hand, forming of heterostructures of ZnO and 5 nanomaterials with the lower in comparison with ZnO band gap is advantageous for optoelectronic applications related to photoactive charge separation in visible and NIR range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most well developed and facile techniques for the deposition of thin metal oxide films on porous materials is atomic layer deposition (ALD) [16,37,38]. This technique allows for the fabrication of highly conformal films of ZnO and other metal oxides over the PSi surface and the production of high-quality nanocomposites in comparison to other methods [4,5,39].…”
Section: Introductionmentioning
confidence: 99%